2011
DOI: 10.1021/ic2016963
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Centered Deltahedral Zintl Ions: Synthesis of [Ni@Sn9]4– by Direct Extraction from Intermetallic Precursors and of the Vertex-Fused Dimer [{Ni@Sn8(μ-Ge)1/2}2]4–

Abstract: Ni-centered deltahedral Sn(9) clusters with a charge of 4-, i.e., [Ni@Sn(9)](4-), were extracted in ethylenediamine in high yield directly from intermetallic precursors with the nominal composition "K(4)Sn(9)Ni(3)". The new endohedral clusters were crystallized and structurally characterized in K[K(18-crown-6)](3)[Ni@Sn(9)]·3benzene (1a, triclinic, P1̅, a = 10.2754(5) Å, b = 19.5442(9) Å, and c = 20.5576(13) Å, α = 73.927(3)°, β = 79.838(4)°, and γ = 84.389(3)°, V = 3899.6(4) Å(3), Z = 2) and K[K(2,2,2-crypt)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 63 publications
7
54
0
Order By: Relevance
“…We already reported that ethylenediamine solutions of the intermetallic compound K 5 Bi 4 react with Ni(PPh 3 ) 2 (CO) 2 to form a number of small intermetalloid clusters such as Bi 3 Ni 4 (CO) 6 3− , Bi 3 Ni 6 (CO) 9 3− , and Ni@ Bi 6 Ni 6 (CO) 8 4− . 17 Of these, the first two anions exhibit bent bismuth trimers with an overall charge of 3−, i.e., each bismuth is formally Bi − .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We already reported that ethylenediamine solutions of the intermetallic compound K 5 Bi 4 react with Ni(PPh 3 ) 2 (CO) 2 to form a number of small intermetalloid clusters such as Bi 3 Ni 4 (CO) 6 3− , Bi 3 Ni 6 (CO) 9 3− , and Ni@ Bi 6 Ni 6 (CO) 8 4− . 17 Of these, the first two anions exhibit bent bismuth trimers with an overall charge of 3−, i.e., each bismuth is formally Bi − .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…One approach is to aggregate the known smaller Bi/Ni/CO clusters Bi 3 Ni 4 (CO) 6 3− , Bi 3 Ni 6 (CO) 9 3− , and Ni@Bi 6 Ni 6 (CO) 8 4− by applying oxidation and deligation. Both processes can be accomplished by simply elevating the temperature of the reaction mixture.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus the clusters are linked by potassium cations to infinite 4-clusters are drawn as polyhedra, hydrogen atoms are omitted for clarity. [7] including empty as well as completely Ni-filled Sn 9 clusters, respectively. Comparison with these two crystal structures reveals that all relevant structural parameters of the new compound are intermediate between the known examples of this structure type (see Supporting Information).…”
Section: Crystal Structuresmentioning
confidence: 99%
“…anions. [7,10] The formation of such dimeric units seems to depend on the presence of a suitable transition metal stabilizing these partially oxidized fused cluster dimers. This assumption is also supported by the lack of observations of unfilled [E 17 ] 5-clusters residing in the center ( Figure 5).…”
Section: Crystal Structuresmentioning
confidence: 99%
See 1 more Smart Citation